Investigation of the implant-supported overdentures in completely edentulous mandibles - Yu-Hwa Pan; Kuan-Wei Chen; Tai-Min Lin; Yang-Ming Chang (Journal of Dental Sciences, 2015)
Background/purpose: This study investigated the cumulative survival rate of the mandibular implant-supported overdentures in patients treated from 2005 to 2014 at the Chang Gung Memorial Hospital Implant Center. Materials and methods: Mandibular implant-supported overdentures were placed in 61 patients (32 males and 29 females) during the period from 2005 to 2014. These patients were categorized into two groups according to the type of attachment system used, namely, Group A and Group B. Group A included 31 patients (17 males and 14 females who received a total of 124 implants) whose denture was retained by a Hader bar and cast ERA attachments, whereas Group B included 30 patients (15 males and 15 females who received a total of 120 implants) whose denture was retained by a Hader bar and bilateral, extension cantilevers with clips. Results: At the end of the follow-up period, 238 implants remained. Among the failed implants, two implants were in Group A (failure rate 2/124 = 1.6%), whereas four implants were in Group B (failure rate 4/120 = 3.3%). Fifty percent (3/6) of the failed implants were placed in the distal anterior mandible and 50% (3/6) were placed in the middle anterior mandible. The condition of the opposing arch was also analyzed in relation to the survival rate. The failure rate among patients with maxillary complete dentures was only 1.6%, whereas those wearing maxillary removable partial dentures had the highest implant failure rate (3/61 = 4.9%). Conclusion: Our results indicate that implant-supported overdentures provide a reliable and effective alternative to conventional complete mandibular dentures. Overdentures with Hader bars and bilateral, cast ERA attachments resulted in fewer prosthetic complications.